Unruptured pregnancy in non-communicating rudimentary horn of uterus: a case report - Sonika, Dahiya; Shobha, Mukherjee (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Pregnancy in a non-communicating rudimentary horn of a uterus is rare. It’s incidence is 1 in 76,000 pregnancies. It is treated as an ectopic pregnancy. Most of the times it is diagnosed after rupture in the late 2nd trimester. Here we present a case, where diagnosis is made prior to the rupture